“HIIT” the ExerCube: Comparing the Effectiveness of Functional High-Intensity Interval Training in Conventional vs. Exergame-Based Training - Martin-Niedecken, Anna Lisa; Mahrer, Andrea; Rogers, Katja; de Bruin, Eling D.; Schättin, Alexandra (Frontiers in Computer Science, 2020)
Regular physical activity is crucial for a physically and mentally healthy lifestyle. Training methods such as high-intensity interval training (HIIT) have become increasingly popular as they enable substantial training effects in little time. HIIT typically involves recurring short phases of close-to-maximal exercise intensity, interspersed with low-intensity recovery phases. Originally mainly practiced via isolated, single-joint movements (conventional HIIT), newer variations include functional multi-joint exercises (fHIIT). While conventional HIIT facilitates many health advantages, fHIIT is considered more beneficial since it activates more muscles, requires more coordination, strength and balance, and mimics more natural tasks which transfer well to daily life. However, fHIIT is a very intense training approach; it requires strong focus and intrinsic motivation to frequently push beyond perceived physical and mental limits. This is a common barrier to exploiting the full potential of this efficient training method. Exergames may facilitate this kind of training due to their playful, immersive, and motivating nature. Yet so far, few studies investigated HIIT exergames - no fHIIT exergames - as hardly any exergame features both 1) an effective concept that is comparable to conventional HIIT training, and 2) an attractive game design to sustain motivation. We believe that this lack of holistic integration of both aspects is partly why currently little evidence exists for long-term motivation and training effects in exergame-based training. Our work addresses this gap through the design of an adaptive fHIIT protocol for the ExerCube, creating a HIIT-level functional fitness exergame. We conducted a within-subjects study to compare objective (physiological) and subjective training intensity induced by the ExerCube and a conventional fHIIT session with young adults. Furthermore, we evaluated participants’ subjective experience including motivation, flow, and enjoyment during both types of training. Our results contribute empirical evidence that exergames could induce fHIIT-level training intensity. While physical exertion was significantly lower, significantly better results were assessed for flow, enjoyment, and motivation as well as for dual-domain training (higher cognitive load). We discuss these results in the context of exergame design for fHIIT-level exercise intensity and provide practical suggestions covering topics such as safety precautions and physical-cognitive load balancing.